Role of homoeopathy of Ayush in dengue fever - Tripathy, Tridibesh; Das, Shankar; Singh, D. P.; Pandey, S. N.; Tripathy, Sanskriti; Tripathy, Anjali; Dwivedi, Rakesh; Gautam, Mohini (International Journal Of Community Medicine And Public Health, 2023)
In 21st century, dengue came to the limelight. Earlier, it was taught that this is one of the eruptive fevers in human beings where in dengue, the eruption appears typically on the 6th day of the fever. Knowledge and approaches to dengue took a paradigm shift in 21st century. It came to be clubbed under the National Vector Borne Disease Control Program. A mosquito borne single stranded RNA virus is the leading cause of arthropod borne viral diseases like dengue globally. All the types of dengue virus are capable of inducing severe diseases like dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). No one wants to be in DHF or DSS stage as these are mortal stages while other stages are morbid. A vector borne disease (VBD) transmitted by mosquito has no specific cure in modern medicine. To add to that, the issue of platelet transfusion that is made universal because of the inherent panic does more harm than good. It is here that homoeopathy has a role to play therapeutically. The article discusses the disease and the related physiology as well as pathology that goes inside the body during an episode of dengue fever. Along with the diagnosis and management approaches, the article elicits the role of homoeopathy through a suggested treatment protocol. Through the inherent properties of homoeopathy such as cost effectiveness, clinical effectiveness and zero side effects, the article proposes large scale application of homoeopathy at all levels.